LA SUPERSTIZIONE ZANDE, by F. Gero. Editrice Nigrizia, via Meloncello, 3/3 Bologna, Italy. 304 pp., 15 musical exs. L.2,200. DEATH AMONG THE AZANDE OF THE SUDAN (Beliefs, Rites and Cult), by F. Gero. Translated from the Italian by W. H. Paxman. Editrice Nigrizia. 184 pp., ill., 13 musical exs., map. L.5,000 - Basil, Brother (International Library of African Music, 1971)
pages: 101
Keywords: African Music